PROGRAM ONE VILLAGE ONE PRODUCT (OVOP) UNTUK MENINGKATKAN DAYA SAING UMKM DI DESA JAYAMEKAR KECAMATAN CIBUGEL KABUPATEN SUMEDANG - Asep Saeful Falah (Bajang Institute, 2024)
The entrepreneurship seminar is an innovation carried out in PKM activities to provide education to the Jayamekar village community, especially in the fields of UMKM and digital marketing. The large number of business actors and the lack of markets in Jayamekar village make competition between business actors increasingly difficult. Therefore, to answer the problems that occur, we provide education to the Jayamekar village community about digital marketing so that the community has a target market other than direct sales. With increasing income from UMKM , the village economy becomes stronger